A Literary Exegetical Analysis of Book of Jonah 3:1-10 - Simon, Shyson Poruthoor (Asian Horizons, 2024)
This article examines the Biblical theme of God’s Call in the book of Jonah. Although there are many studies about the life of Jonah and the song of Jonah, this Biblical exegesis focuses on the Call of Jonah for the Universal love of God. In other words, this study explores God’s mercy on a Gentile Community with the motif of salvation for everyone. The contextual, formal, and detailed analysis and the theological reflections and interpretations evoke the reader’s ability to see the passage from another perspective. The author’s work also helps readers to understand how a community’s or an individual’s true repentance might stop the transient disasters that the Supreme Author has already prepared.